FENOMENA PEMBONCENG GRATIS (FREE RIDERS) DI SEKITAR KOTA BARU BUMI SERPONG DAMAI (BSD CITY) - Rendy Adriyan Diningrat (Diponegoro University, 2018)
The success of Kota Baru Bumi Serpong Damai (BSD City) as a new growth center triggers the development of free riders in the surrounding area. One of their form is small-scale housings which are riding the new town’s infrastructure. Using a qualitative method, this paper takes part in revealing this phenomenon deeper, especially in terms of motivation and behavior. The discourse will emphasize the urgency of free riders’ management, both their positives and negatives, to keep the new town development goals inclusive and sustainable.